E4orf1 as a key modulator in oncogenesis and of metabolism in Adenovirus infection - Hernández-Magaña, Leidy Erandy; Mosqueda-Gracida, Alfredo; Cruz-Holguín, Víctor Javier; Martínez-Castillo, Macario; Fuentes-Pananá, Ezequiel M.; Rozmyslowicz, Tomasz; León-Juárez, Moisés; Arévalo-Romero, Haruki (Frontiers in Virology, 2023)
Human Adenoviruses are a diverse family of viruses that can infect a variety of tissues causing acute or persistent infection. As viruses hijack cellular functions to promote viral progeny, they induce numerous cellular alterations. Recent research has shed light on the functions of viral proteins in orchestrating viral production, revealing that many of these functions overlap with oncogenesis or metabolic disruption. Studies of the Adenovirus family have identified oncogenic members such as Ad-2, 5, 9, and 12, as well as Ad-36, which is most extensively studied for its ability to induce metabolic alterations. Specifically, Adenoviruses encode a gene product known as early region 4 open reading frame 1 (E4orf1) that has emerged as an oncoprotein and regulator of metabolism, depending on the linage of the infected host cell. This article aims to provide insight into the functions of viral protein, and their overlapping similarities between the oncogenic process and cell metabolism.